Modal analysis and harmonic response analysis of energy-absorbing and anti-scouring columns - Tang, Zhi; Wu, Hao; Wu, Zhiwei; Jia, Dunwei; Fu, Yuejia (Frontiers in Earth Science, 2023)
Many field observations have found that damage to the support did not increase with the magnitude of the impact ground pressure. To enhance the impact protection performance of “support and surrounding rock” system. From the perspective of preventing the resonance of the “support and surrounding rock” system, the dynamic response of energy-absorbing and anti-scouring column is studied. Using the block theory, a dynamic model of the roadway enclosure-absorbing anti-scouring column under impact loading was established, and the dynamic response equation of the rock block at the support end was obtained. Based on the structural dynamics and Love shell theory, the characteristic equations of the energy-absorbing and anti-scouring column were derived, and the theoretical equations for the natural frequency and vibration mode function of the energy-absorbing and anti-scouring column were obtained. The ABAQUS numerical simulation method was used to carry out pre-stress modal analysis and harmonious response analysis of energy-absorbing and anti-scouring columns and conventional columns. We obtained the natural frequencies and vibration modes of the two columns and analyzed the effect of the setting load on the modalities of the columns. The column dynamic response law was determined by monitoring the displacement and velocity response curves at different positions. The results show that the natural frequency and vibration mode of the energy-absorbing and anti-scouring column are related to the density, elastic modulus, and length. The vibration of the energy-absorbing and anti-scouring column has two forms: beam vibration mode and cylindrical shell vibration mode, and the first four orders of vibration mode are transverse bend. The setting load has a small effect on the natural frequency and vibration mode of both types of columns, where the natural frequency decreases as the setting load increases. When the excitation frequency is close to the vibration frequency of the surrounding rock, the radial, axial, and circumferential response amplitudes of the primary and secondary columns of the energy-absorbing and anti-scouring column are the largest. Reinforcement and strengthening measures should be implemented to reduce the column deformation amplitude.